Nardulli, Ed., International Perspectives On Contemporary Democracy - Frusetta, James (Teaching History: A Journal of Methods, 2009)
This collection of essays explores the causes for the spread of democracy over the past two decades, and the prospects for its further spread in the twenty-first century. Roughly half of the collection engages democratization theory and recent cases of the spread of democracy, with the other half considering the challenges or possibilities of globalization for democratic governance. To the editor's considerable credit, the collection achieves the rare goal of bringing together essays that engage each other, are written clearly and cleanly so as to be accessible to the non-specialist, and contribute to the scholarly agenda. In this light, the volume is highly recommended for history teachers of recent global history, U.S. foreign policy since 1945, and specialists on democracy or political ideology.